Neuropsychological Investigation of Anterior and Posterior Cortical Function in Early-Stage Probable Alzheimer’s Disease - P. Broks; C. Lines; L. Atchison; J. Challenor; M. Traub; C. Foster; H. Sagar (Behavioural Neurology)
In vivo neuroimaging studies have generally indicated a greater involvement of posterior cortical areas in early-stage dementia of the Alzheimer type (DAT) relative to frontal involvement. By contrast, some recent neuropsychological studies have shown that DAT patients perform poorly in frontal lobe tasks even in the early stages of the disease, although there is disagreement as to whether this necessarily implicates frontal pathology. The main aim of this study was to examine the hypothesis prompted by both neuroimaging studies and the traditional clinical conception of the disease, that, compared with the functioning of posterior association cortex, executive functions (thought to depend on frontal lobe integrity) are relatively spared in the early stages of DAT. A group of patients with a diagnosis of early-stage, probable DAT (n = 17) was compared with age- and IQ-matched controls (n = 17) across a range of neuropsychological tasks presumed to exercise frontal or temporoparietal functions. A profile of strengths and weaknesses was observed across ‘anterior’ and ‘posterior’ cognitive tests, including dissociations among some tests of temporoparietal function, in particular visual object perception (impaired) and spatial analysis skills (intact). Thus there was little support for the notion that the disease progresses cortically in a posterior-to-anterior direction. Possible reasons for the discrepancy between neurophysiological and neuropsychological observations are discussed, including the possibility that neuropsychological tests do not provide a valid indication of regional brain function when used in the context of DAT. Caution is urged in the clinical application of ‘frontal lobe tests’ for the differential diagnosis of DAT.